Ceramsite preparation method and ceramsite
By mixing titanium gypsum and green alum, drying and ball milling, fine powder is prepared, and then ceramic granules are manufactured through the ballmaking process, the resource utilization problem of titanium dioxide by-products of sulfuric acid method is solved, and the low-cost ceramic preparation is achieved and the large-scale utilization of resources.
Patent Information
- Application Number
- CN202411720175.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-21
AI Technical Summary
The prior art is difficult to effectively utilize the titanium dioxide by-products of titanium dioxide in sulfuric acid method, resulting in waste of resources and high manufacturing costs.
After mixing titanium gypsum and green alum, drying and dehydrating and ball milling, fine powder is prepared, and then different sizes of ceratops are made through the balling process, and different sizes of ceratops are mixed in proportion to achieve an optimized grading.
The large-scale utilization of titanium gypsum and green alum has been achieved, which reduces manufacturing costs and provides low-cost lightweight ceramic products.
Smart Images

Figure CN119490317A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of material preparation, and in particular to a preparation method of ceramsite and the ceramsite. Background Art
[0002] The main byproducts of the sulfuric acid process for titanium dioxide are gypsum and ferrous sulfate heptahydrate. For every ton of titanium dioxide produced, 3-4 tons of gypsum and 2-3 tons of ferrous sulfate are produced, resulting in a massive production volume. Currently, the resource utilization of these byproducts is extremely difficult, presenting a key environmental challenge hindering the development of titanium dioxide production. Finding a way to scale up their utilization is urgently needed.
[0003] Lightweight ceramsite is a primary building material, primarily used in thermal insulation concrete, lightweight wall panels, lightweight building blocks, permeable flooring, and paving bricks. Commonly used ceramsite products include sintered lightweight ceramsite and cement-based lightweight ceramsite. These products are relatively expensive to manufacture, placing significant pressure on downstream users.
[0004] Currently, there are technologies for producing lightweight ceramsite using desulfurized gypsum, titanium gypsum, phosphogypsum, and other raw materials. The main process involves pre-treating gypsum slag to produce α-high-strength gypsum powder, which is then pelletized and pressed into gypsum-based ceramsite. However, this process is costly and unsuitable for large-scale production. Summary of the Invention
[0005] In view of this, in order to overcome at least one aspect of the above problems, an embodiment of the present invention provides a method for preparing ceramsite, comprising the following steps: mixing titanium gypsum and green vitriol to obtain a mixture; drying and dehydrating the mixture and ball-milling the mixture to obtain fine powder; Using the fine powder to produce ceramsite of different sizes; Mix different sizes of expanded clay in proportion according to different gradings.
[0006] In some embodiments, the mixture of titanium gypsum and green vitriol is further comprised of: The mixture is obtained by mixing 50-90% of titanium gypsum and 10-50% of green vitriol according to mass percentage.
[0007] In some embodiments, the mixture is dried, dehydrated, and ball-milled to obtain a fine powder, further comprising: The mixture is dried and dehydrated at 150° C. to 200° C.
[0008] In some embodiments, the mixture is dried, dehydrated, and ball-milled to obtain a fine powder, further comprising: The dried and dehydrated mixture was ground into a fine powder of 250-350 mesh using a tubular ball mill.
[0009] In some embodiments, the method of using the fine powder to produce ceramsite of different sizes further comprises: The fine powder is made into ceramsite of different sizes using a disc pelletizer, and 10-20% of water is added according to mass percentage.
[0010] In some embodiments, further comprising: Add 0.5~2% waterproofing agent by mass.
[0011] In some embodiments, the water repellent is an organic water repellent.
[0012] In some embodiments, further comprising: The ceramsite is immersed in a waterproofing agent solution so that the outer shell of the ceramsite is coated with a layer of waterproofing agent.
[0013] In some embodiments, the titanium gypsum comprises at least 60% CaSO4·2H2O, 5-10% Fe2O3, 2-5% SiO2, and the remaining impurities; The green vitriol comprises at least 90% of FeSO4·7H2O, 3-5% of MgSO4 and other impurities.
[0014] Based on the same inventive concept, according to another aspect of the present invention, an embodiment of the present invention further provides a ceramsite, which is prepared by the following method: mixing titanium gypsum and green vitriol to obtain a mixture; drying and dehydrating the mixture and ball-milling the mixture to obtain fine powder; Using the fine powder to produce ceramsite of different sizes; Mix different sizes of expanded clay in proportion according to different gradings.
[0015] In some embodiments, the mixture of titanium gypsum and green vitriol is further comprised of: The mixture is obtained by mixing 50-90% of titanium gypsum and 10-50% of green vitriol according to mass percentage.
[0016] In some embodiments, the mixture is dried, dehydrated, and ball-milled to obtain a fine powder, further comprising: The mixture is dried and dehydrated at 150° C. to 200° C.
[0017] In some embodiments, the mixture is dried, dehydrated, and ball-milled to obtain a fine powder, further comprising: The dried and dehydrated mixture was ground into a fine powder of 250-350 mesh using a tubular ball mill.
[0018] In some embodiments, the method of using the fine powder to produce ceramsite of different sizes further comprises: The fine powder is made into ceramsite of different sizes using a disc pelletizer, and 10-20% of water is added according to mass percentage.
[0019] In some embodiments, further comprising: Add 0.5~2% waterproofing agent by mass.
[0020] In some embodiments, the water repellent is an organic water repellent.
[0021] In some embodiments, further comprising: The ceramsite is immersed in a waterproofing agent solution so that the outer shell of the ceramsite is coated with a layer of waterproofing agent.
[0022] In some embodiments, the titanium gypsum comprises at least 60% CaSO4·2H2O, 5-10% Fe2O3, 2-5% SiO2, and the remaining impurities; The green vitriol comprises at least 90% of FeSO4·7H2O, 3-5% of MgSO4 and other impurities.
[0023] The present invention has the following beneficial technical effects: The proposed method uses titanium gypsum and green vitriol, byproducts of the sulfuric acid process for titanium dioxide, as primary raw materials. By utilizing the properties of gypsum and green vitriol that absorb free water and recrystallize to produce a strong matrix, the method produces lightweight ceramsite, a primary product for building materials, through batching, mixing, drying, ball milling, and pelletizing. This method not only provides low-cost lightweight ceramsite products for downstream building materials users, but also enables the large-scale utilization of titanium gypsum and green vitriol, byproducts of the sulfuric acid process for titanium dioxide. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying any creative work.
[0025] Figure 1 A schematic flow chart of a method for preparing ceramsite provided by an embodiment of the present invention; Figure 2 The present invention provides a flowchart of a method for preparing ceramsite according to an embodiment of the present invention. DETAILED DESCRIPTION
[0026] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the embodiments of the present invention are further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings.
[0027] It should be noted that all expressions using "first" and "second" in the embodiments of the present invention are for distinguishing two non-identical entities with the same name or non-identical parameters. It can be seen that "first" and "second" are only for the convenience of expression and should not be understood as limitations on the embodiments of the present invention. Subsequent embodiments will not explain this one by one.
[0028] According to one aspect of the present invention, an embodiment of the present invention provides a method for preparing ceramsite, such as Figure 1 As shown, it may include the steps of: mixing titanium gypsum and green vitriol to obtain a mixture; drying and dehydrating the mixture and ball-milling the mixture to obtain fine powder; Using the fine powder to produce ceramsite of different sizes; Mix different sizes of expanded clay in proportion according to different gradings.
[0029] The proposed method uses titanium gypsum and green vitriol, byproducts of the sulfuric acid process for titanium dioxide, as primary raw materials. Leveraging the ability of gypsum and green vitriol to absorb free water and recrystallize, creating a strong matrix, the method produces lightweight ceramsite, a primary product for building materials, through batching, mixing, drying, ball milling, and pelletizing. This method not only provides low-cost lightweight ceramsite for downstream building material users, but also enables the large-scale utilization of titanium gypsum and green vitriol, byproducts of the sulfuric acid process for titanium dioxide. Furthermore, compared with existing processes, this method offers lower costs and higher solid waste resource utilization.
[0030] In some embodiments, the mixture of titanium gypsum and green vitriol is further comprised of: The mixture is obtained by mixing 50-90% of titanium gypsum and 10-50% of green vitriol according to mass percentage.
[0031] In some embodiments, the mixture is dried, dehydrated, and ball-milled to obtain a fine powder, further comprising: The mixture is dried and dehydrated at 150° C. to 200° C.
[0032] In some embodiments, the mixture is dried, dehydrated, and ball-milled to obtain a fine powder, further comprising: The dried and dehydrated mixture was ground into a fine powder of 250-350 mesh using a tubular ball mill.
[0033] In some embodiments, the method of using the fine powder to produce ceramsite of different sizes further comprises: The fine powder is made into ceramsite of different sizes using a disc pelletizer, and 10-20% of water is added according to mass percentage.
[0034] In some embodiments, further comprising: Add 0.5~2% waterproofing agent by mass.
[0035] In some embodiments, the water repellent is an organic water repellent.
[0036] In some embodiments, further comprising: The ceramsite is immersed in a waterproofing agent solution so that the outer shell of the ceramsite is coated with a layer of waterproofing agent.
[0037] In some embodiments, the titanium gypsum comprises at least 60% CaSO4·2H2O, 5-10% Fe2O3, 2-5% SiO2, and the remaining impurities; The green vitriol comprises at least 90% of FeSO4·7H2O, 3-5% of MgSO4 and other impurities.
[0038] Specifically, such as Figure 2 As shown, titanium gypsum slag and green vitriol are first mixed according to the proportions, and then uniformly mixed using a double-screw mixer. The raw material ratio (by mass percentage) can be 50-90% titanium gypsum and 10-50% green vitriol. The titanium gypsum contains at least 60% CaSO4·2H2O, 5-10% Fe2O3, and 2-5% SiO2. The green vitriol contains at least 90% FeSO4·7H2O, 3-5% MgSO4, and other impurities, such as a small amount of TiOSO4.
[0039] The mixed materials are then transported into the drying drum for drying and dehydration at 200°C.
[0040] The dehydration process can be: CaSO4·2H2O→CaSO4·0.5H2O+ 1.5H2O FeSO4·7H2O→FeSO4·H2O+ 6H2O The dehydrated product is then transported to a tubular ball mill and ground into a 300-mesh fine powder. The fine powder is then pelletized using a disc pelletizer to produce ceramsite of varying gradations, with water and waterproofing agents added during the process.
[0041] The recrystallization process can be: CaSO4·0.5H2O+ 1.5H2O→CaSO4·2H2O FeSO4·H2O+ 6H2O→FeSO4·7H2O 4FeSO4+ O2+ 2H2O→4Fe(OH)SO4 4Fe(OH)SO4→4Fe(OH)3+ 4SO4 2- 4FeSO4+ 6H2O + O2→4Fe(OH)3+ 4H2SO4 Fe(OH)3+Ca 2+ →CaFe2O4+ 3H2O CaSO4·2H2O+Fe(OH)3→CaSO4·Fe(OH)3+ 2H2O The finished ceramsite is then immersed in a waterproofing solution to coat the outer shell with a layer of waterproofing agent, achieving secondary waterproofing. Finally, the ceramsite of different grades is air-dried separately. The graded ceramsite is assembled according to user requirements and sold directly.
[0042] The final ceramsite has a compressive strength of 0.3~0.5kN and an apparent density of 0.8~1.2g / cm 3 , the bulk density can reach 0.5~0.8g / cm 3 , the softening coefficient reaches above 0.90.
[0043] In some embodiments, the ceramsite obtained by the solution proposed by the present invention can be applied to building materials such as thermal insulation concrete, lightweight building wall panels, lightweight building blocks, permeable floors, and pavement bricks.
[0044] Example 1 First, titanium gypsum slag and green vitriol are mixed in a ratio of 50% and 50%, and then the raw materials are mixed evenly using a double-screw mixer. The mixed material is conveyed into a drying drum and dried and dehydrated at 150°C. The dehydrated product is conveyed to a tubular ball mill and ground into a fine powder of 250 mesh. The fine powder is used to make ceramsite of different gradations using a disc ball making machine. During the process, 15% water and 2% waterproofing agent are added. The ceramsite is dried. The single ball compressive strength of the ceramsite is measured to be 0.48kN, and the apparent density of the ceramsite is 1.0g / cm 3 The bulk density of ceramsite is 0.6g / cm3 and the softening coefficient of ceramsite is 0.95.
[0045] Example 2 First, titanium gypsum slag and green vitriol are mixed in the proportion of 90% and 10%, and then the raw materials are evenly mixed using a double-screw mixer. The mixed material is conveyed into a drying drum and dried and dehydrated at 200°C. The dehydrated product is conveyed to a tubular ball mill and ground into a 300-mesh fine powder. The fine powder is used to make ceramsite of different gradations using a disc ball making machine, and 20% water and 1% waterproofing agent are added during the process. The ceramsite is dried. The single-ball compressive strength of the ceramsite is measured to be 0.35kN, and the apparent density of the ceramsite is 1.2g / cm 3 The bulk density of ceramsite is 0.8g / cm3 and the softening coefficient of ceramsite is 0.94.
[0046] Example 3 First, titanium gypsum slag and green vitriol are mixed in the proportion of 70% and 30%, and then the raw materials are mixed evenly using a double-screw mixer. The mixed materials are conveyed into a drying drum and dried and dehydrated at 180°C. The dehydrated product is conveyed to a tubular ball mill and ground into a 350-mesh fine powder. The fine powder is used to make ceramsite of different gradations using a disc ball making machine. During the process, 10% water and 0.5% waterproofing agent are added. The ceramsite is dried. The single-ball compressive strength of the ceramsite is measured to be 0.42kN, and the apparent density of the ceramsite is 0.85g / cm 3 The bulk density of ceramsite is 0.7g / cm3 and the softening coefficient of ceramsite is 0.92.
[0047] The proposed method uses titanium gypsum and green vitriol, byproducts of the sulfuric acid process for titanium dioxide, as primary raw materials. Leveraging the ability of gypsum and green vitriol to absorb free water and recrystallize, creating a strong matrix, the method uses batching, mixing, drying, ball milling, and pelletizing to produce lightweight ceramsite, a primary product for building materials. This method not only provides low-cost lightweight ceramsite for downstream building material users, but also enables the large-scale utilization of titanium gypsum and green vitriol, byproducts of the sulfuric acid process.
[0048] Based on the same inventive concept, according to another aspect of the present invention, an embodiment of the present invention further provides a ceramsite, which is prepared by the following method: mixing titanium gypsum and green vitriol to obtain a mixture; drying and dehydrating the mixture and ball-milling the mixture to obtain fine powder; Using the fine powder to produce ceramsite of different sizes; Mix different sizes of expanded clay in proportion according to different gradings.
[0049] The proposed method uses titanium gypsum and green vitriol, byproducts of the sulfuric acid process for titanium dioxide, as primary raw materials. Leveraging the ability of gypsum and green vitriol to absorb free water and recrystallize, creating a strong matrix, the method uses batching, mixing, drying, ball milling, and pelletizing to produce lightweight ceramsite, a primary product for building materials. This method not only provides low-cost lightweight ceramsite for downstream building material users, but also enables the large-scale utilization of titanium gypsum and green vitriol, byproducts of the sulfuric acid process.
[0050] In some embodiments, the mixture of titanium gypsum and green vitriol is further comprised of: The mixture is obtained by mixing 50-90% of titanium gypsum and 10-50% of green vitriol according to mass percentage.
[0051] In some embodiments, the mixture is dried, dehydrated, and ball-milled to obtain a fine powder, further comprising: The mixture is dried and dehydrated at 150° C. to 200° C.
[0052] In some embodiments, the mixture is dried, dehydrated, and ball-milled to obtain a fine powder, further comprising: The dried and dehydrated mixture was ground into a fine powder of 250-350 mesh using a tubular ball mill.
[0053] In some embodiments, the method of using the fine powder to produce ceramsite of different sizes further comprises: The fine powder is made into ceramsite of different sizes using a disc pelletizer, and 10-20% of water is added according to mass percentage.
[0054] In some embodiments, further comprising: Add 0.5~2% waterproofing agent by mass.
[0055] In some embodiments, the water repellent is an organic water repellent.
[0056] In some embodiments, further comprising: The ceramsite is immersed in a waterproofing agent solution so that the outer shell of the ceramsite is coated with a layer of waterproofing agent.
[0057] In some embodiments, the titanium gypsum comprises at least 60% CaSO4·2H2O, 5-10% Fe2O3, 2-5% SiO2, and the remaining impurities; The green vitriol comprises at least 90% of FeSO4·7H2O, 3-5% of MgSO4 and other impurities.
[0058] Specifically, such as Figure 2 As shown, titanium gypsum slag and green vitriol are first mixed according to the proportions, and then uniformly mixed using a double-screw mixer. The raw material ratio (by mass percentage) can be 50-90% titanium gypsum and 10-50% green vitriol. The titanium gypsum contains at least 60% CaSO4·2H2O, 5-10% Fe2O3, and 2-5% SiO2. The green vitriol contains at least 90% FeSO4·7H2O, 3-5% MgSO4, and other impurities, such as a small amount of TiOSO4.
[0059] The mixed materials are then transported into the drying drum for drying and dehydration at 200°C.
[0060] The dehydration process can be: CaSO4·2H2O→CaSO4·0.5H2O+ 1.5H2O FeSO4·7H2O→FeSO4·H2O+ 6H2O The dehydrated product is then transported to a tubular ball mill and ground into a 300-mesh fine powder. The fine powder is then pelletized using a disc pelletizer to produce ceramsite of varying gradations, with water and waterproofing agents added during the process.
[0061] The recrystallization process can be: CaSO4·0.5H2O+ 1.5H2O→CaSO4·2H2O FeSO4·H2O+ 6H2O→FeSO4·7H2O 4FeSO4+ O2+ 2H2O→4Fe(OH)SO4 4Fe(OH)SO4→4Fe(OH)3+ 4SO4 2- 4FeSO4+ 6H2O + O2→4Fe(OH)3+ 4H2SO4 Fe(OH)3+Ca 2+ →CaFe2O4+ 3H2O CaSO4·2H2O+Fe(OH)3→CaSO4·Fe(OH)3+ 2H2O The finished ceramsite is then immersed in a waterproofing solution to coat the outer shell with a layer of waterproofing agent, achieving secondary waterproofing. Finally, the ceramsite of different grades is air-dried separately. The graded ceramsite is assembled according to user requirements and sold directly.
[0062] The final ceramsite has a compressive strength of 0.3~0.5kN and an apparent density of 0.8~1.2 g / cm 3 , the bulk density can reach 0.5~0.8g / cm 3 , the softening coefficient reaches above 0.90.
[0063] In some embodiments, the ceramsite obtained by the solution proposed by the present invention can be applied to building materials such as thermal insulation concrete, lightweight building wall panels, lightweight building blocks, permeable floors, and pavement bricks.
[0064] The above are exemplary embodiments disclosed in the present invention, but it should be noted that various changes and modifications may be made without departing from the scope of the embodiments disclosed in the claims. The functions, steps and / or actions of the method claims according to the disclosed embodiments described herein do not need to be performed in any particular order. In addition, although the elements disclosed in the embodiments of the present invention may be described or required in individual form, they may also be understood as multiple unless expressly limited to the singular.
[0065] It should be understood that, as used herein, the singular forms "a" and "an" are intended to include the plural forms as well, unless the context clearly supports an exception. It should also be understood that, as used herein, "and / or" is intended to include any and all possible combinations of one or more of the associated listed items.
[0066] The serial numbers of the embodiments disclosed in the above embodiments of the present invention are only for description and do not represent the advantages or disadvantages of the embodiments.
[0067] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to limit the scope of the disclosure of the present invention (including the claims) to these examples. Within the spirit of the present invention, the technical features of the above embodiments or different embodiments may be combined, and many other variations exist in different aspects of the above embodiments, which are not provided in detail for the sake of clarity. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing ceramsite, characterized in that: The following steps are involved: mixing titanium gypsum and green vitriol to obtain a mixture; Drying, dehydrating and ball-milling the mixture to obtain fine powder; Using the fine powder to manufacture ceramsite of different sizes; Mix expanded clay of different sizes in proportion according to different gradings.
2. The method according to claim 1, characterized in that The mixture is obtained by mixing titanium gypsum and green vitriol, further comprising: According to mass percentage, 50-90% of titanium gypsum and 10-50% of green vitriol are mixed to obtain a mixture.
3. The method according to claim 1, characterized in that The mixture is dried, dehydrated and ball-milled to obtain fine powder, further comprising: The mixture is dried and dehydrated at 150°C-200°C.
4. The method according to claim 1, characterized in that The mixture is dried, dehydrated and ball-milled to obtain fine powder, further comprising: The dried and dehydrated mixture is ground into fine powder of 250-350 meshes using a tubular ball mill.
5. The method according to claim 1, characterized in that The method of using the fine powder to produce ceramsite of different sizes further comprises: The fine powder is made into ceramsite of different sizes by using a disc pelletizing machine, and 10-20% of water is added according to mass percentage.
6. The method according to claim 5, characterized in that Also includes: Add 0.5~2% waterproofing agent by mass.
7. The method according to claim 6, characterized in that The waterproofing agent is an organic waterproofing agent.
8. The method according to claim 5, characterized in that Also includes: The ceramsite is immersed in a waterproofing agent solution so that the outer shell of the ceramsite is coated with a layer of waterproofing agent.
9. The method according to claim 1, characterized in that The titanium gypsum includes at least 60% of CaSO4·2H2O, 5-10% of Fe2O3, 2-5% of SiO2 and other impurities; The green vitriol comprises at least 90% of FeSO4·7H2O, 3-5% of MgSO4 and other impurities.
10. A ceramsite, characterized in that: The ceramsite is prepared by the method according to any one of claims 1 to 9.